(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
In regenerative medicine, nanotechnology plays a vital role in the diagnosis, the delivery of therapeutic drugs and the treatment of many diseases and disorders. Due to the growing need to develop environmentally friendly technologies in material synthesis, the biosynthesis of Iron Oxide Nanoparticles (IOP) has received considerable attention over the past decades. Therefore, the community is now looking back for traditional medicines for various diseases after the practice of allopathic drugs with tremendous side effects. There are an increasing number of biomedical applications for iron oxide nanoparticles; as such uses are essential for in-vitro characterisation and in-vivo to ensure the bio-safety of these particles. The main complication of diabetes due to frequent lipid peroxidation is liver damage and renal dysfunction, but treatment with Leucas aspera has a pronounced effect on these indicators, which protects the organs from further damage. The current research supports the traditional use of Leucas aspera against diabetes mellitus and cancer, as well as the safety, effectiveness and potency of Leucas aspera leaf extract's anti-diabetic and anti-cancer effect in the in-vivo model. The overall results reveal that Leucas aspera has the potential and can be a candidate of choice without side effect.